Revolutionen mot kapitalet - Anrup, Roland (Arbejderhistorie, 2026)
The article deals with Lenin's political strategy during the changing conjunctures of the Russian revolution. However, this is not primarily a study of these conjunctures per se or of the influence Lenin came to have during them. The purpose is rather to show through an examination of Lenin's writings how his discourse in practical form chisels out a concept of conjuncture which in fact means a theoretical revolution within the marxism of the time. In his political practice, although not in an explicit theoretical form, lenin eﬀected a radical break with the teleological notions which, both in its reformist and in its pretended revolutionary variant, marked and characterized the Second international and which after lenin came to dominate also in the Third international.